Konsekuensi Yuridis Diskresi Pejabat Syahbandar Pelabuhan Manado Terhadap Penetapan Lokasi Kegiatan Bongkar Muat di Kecamatan Malalayang Yang Berdampak Hilangnya Pendapatan Negara - Pattrick William Renaldy Malangkas; Ronald J Mawuntu; Emma V T Senewe (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2023)
Discretion or policy must of course be in line with Law Number 30 of 2014 concerning Government Administration providing clear parameters regarding the use of discretion by Government Officials so that it can be measured with certainty which discretion is permitted to be issued and implemented and which discretion is deviant or against the law. This study uses normative juridical legal research with a conceptual approach. The results of this study indicate that the permit approval for the use of the coastline of Malalayang Satu Village, Malalayang District, which is used as an activity for loading and unloading of excavated material c outside the port area, does not have an official permit or is illegal. The approval for granting permits conflicts with North Sulawesi Provincial Government Regulation Number 1 of 2014 concerning the spatial plan for the province of North Sulawesi for 2014 – 2034. in tourism zoning so that the Discretion or policy of the Head of the Manado Port Authority and Harbormaster Office regarding granting permits to utilize the coastline of Malalayang Satu Exit, Malalayang District becomes invalid